A screen for bacterial endosymbionts in the model organisms Tribolium castaneum, T. confusum, Callosobruchus maculatus, and related species - Goodacre, S.L.; Fricke, C.; Martin, O.Y (Wiley, 2015)
Reproductive parasites such as Wolbachia are extremely widespread amongst the arthropods and can have a large influence over the reproduction and fitness of their hosts. Undetected infections could thus confound the results of a wide range of studies that focus on aspects of host behavior, reproduction, fitness, and degrees of reproductive isolation. This potential problem has already been underlined by work investigating the incidence of Wolbachia infections in stocks of the model system Drosophila melanogaster. Here we survey a range of lab stocks of further commonly used model arthropods, focusing especially on the flour beetles Tribolium castaneum and Tribolium confusum, the cowpea weevil Callosobruchus maculatus and related species (Coleoptera: Tenebrionidae and Bruchidae). These species are widespread stored product pests so knowledge of infections with symbionts further has potential use in informing biocontrol measures. Beetles were assessed for infection with 3 known microbial reproductive parasites: Wolbachia, Rickettsia, Spiroplasma. Infections with some of these microbes were found in some of the lab stocks studied, although overall infections were relatively rare. The consequences of finding infections in these or other species and the type of previous studies likely to be affected most are discussed.